Analyzing Market Exploitation and Market Exploration Dyad for Marketing Strategy Implementation Effectiveness in Malaysian Fertilizer Industry: A Conceptual Paper - AZIZ, NORAZLINA; ABDUL MAJID, IZAIDIN; MD NORDIN, SHAHRINA; KAMALUDIN, HASFARIZAL; LAI, FONG WOON (2013)
Analyzing the marketing strategy elements that influence the effectiveness of its implementation has been the subject of sizeable empirical research. The purpose of this paper is to address simultaneous management of market exploitation and market exploration in the marketing strategy on implementation effectiveness among the most relevant new product introduction success factors in Malaysian fertilizer industry. The proposed framework has theoretical significance in filling the gap in the body of knowledge in the implementation of marketing strategy in the Malaysian fertilizer industry. This paper discusses issues in relation to the role of marketing strategy which have profound impact on organizational implementation effectiveness.